A Simple Clinical Pre-procedure Risk Model for Predicting Thrombocytopenia Associated With Periprocedural Use of Tirofiban in Patients Undergoing Percutaneous Coronary Intervention - Yi, Yi-Hu; Yin, Wen-Jun; Gu, Zhi-Chun; Fang, Wei-Jin; Li, Dai-Yang; Hu, Can; Liu, Kun; Ma, Rong-Rong; Zhou, Ling-Yun (Frontiers in Pharmacology, 2018)
Background: No risk model for predicting thrombocytopenia associated with periprocedural tirofiban exposure is available. The purpose of this study was to develop a simple clinical pre-procedure risk model based on pre-procedural characteristics for early prediction of thrombocytopenia before patients were exposed to tirofiban. Methods: The series included 1862 patients who underwent percutaneous coronary intervention with tirofiban exposure. Baseline demographic and clinical characteristics were collected from the hospital information system on admission. The earliest pro-procedural platelets within 72 hours were used to evaluate the thrombocytopenia incidence. Risk factors associated with thrombocytopenia in patients with tirofiban exposure were investigated by univariable and multivariable analyses. Locally weighted scatterplot smoothing procedure was used to identify the cut points for the numeric variables. The discriminatory power of the scoring system was assessed with the receiver operating characteristic (ROC) curve analysis. Results: The occurrence of thrombocytopenia was 4.02% (75 of 1862), 4.01%(56 of 1396), and 4.08% (19 of 466) in the overall, developmental, and validation data sets, respectively. The risk score was developed based on 5 independent predictors: age≥65 y, white blood cell ≥12×109/L, diabetes mellitus, congestive heart failure, and chronic kidney disease. This tool was well calibrated (Hosmer Lemeshow □□2 =6.914; P=0.546) and good discrimination was well obtained in validation data set (C-statistic, 0.82). Conclusions: The clinical pre-procedure risk model is a simple and accurate tool for early identification of high-risk patients of thrombocytopenia before tirofiban exposure, allowing for timely and appropriate intervention.